Currents simulation in the Malacca Straits by Using Three-Dimensional Numerical Model (Universiti Kebangsaan Malaysia, 2010)
motion (Navier-Stokes equation) with the following driving forces: tides, wind of National Centers for Environmental Prediction (NCEP) for year of 2007, salinity and temperature. The equation of motion was solved by means of Hamburg Shelf Ocean Model (HAMSOM). The results for both southwest and northeast monsoon were explained and discussed. The simulation results both for February and August 2007 were relatively similar. Current surface simulation in the Malacca Straits agrees well with the current pattern of previous works. The magnitude of current was between 10-70 cm/s to the northwest. While at the layer 30-50 m in the Malacca Straits, the currents have the magnitude of 10-30 cm/s towards northwest. For the bottom current, the current speed was 0-20 cm/s towards northwest. For the surface and 30-50 m layer, generally the current magnitudes were greater in February compared to those in August. While for the bottom layer, the current magnitudes between February and August were relatively the same.